1956 and all that : the making of modern British drama - Rebellato, Dan, 1968- (Routledge, 1999)
It is said that British Drama was shockingly lifted out of the doldrums by the 'revolutionary' appearance of John Osborne's Look Back in Anger at the Royal Court in May 1956. But had the theatre been as ephemeral and effeminate as the Angry Young Men claimed? Was the era of Terence Rattigan and 'Binkie' Beaumont as repressed and closeted as it seems? In this bold and fascinating challenge to the received wisdom of the last forty years of theatrical history, Dan Rebellato uncovers a different story altogether. It is one where Britain's declining Empire and increasing panic over the.